The Effect of Agricultural Subsidies on Rice Productivity and Prices in Southeast Asia: A Panel Regression Study - Sopian, Andi; Fitrianti, Retno; Yakub, Andryirawan; Sapanang, A. Baso Aditya; Fitrianti, A. Nur; Hamka, Hamka (International Journal of Humanities, Education, and Social Sciences, 2024)
Agricultural subsidies have become a common instrument used by countries in the Southeast Asian Region to support farmers, increase food production, and control prices. However, the effectiveness and long-term impact of these subsidies are still a hot debate in the economic literature. The purpose of this study is to analyze how agricultural subsidies affect rice productivity and rice prices in three Southeast Asian countries: Indonesia, Thailand, and Vietnam, during the period 2020-2023. The method used in this study is panel data analysis with a fixed effect to control the variation between countries that is not observed. Panel regression analysis was carried out to identify the relationship between agricultural subsidies and the two dependent variables. The F-test and Chi-square test are used to test for the existence of fixed effects, while the cross-section dependency test is used to check the residual correlation between countries. The results of this study show that the regression results of the panel show that agricultural subsidies have a significant negative impact on rice productivity (Y1), which may reflect inefficient resource allocation or the presence of market distortions that hinder productivity increase. In contrast, subsidies have a significant positive impact on rice prices (Y2), suggesting that subsidies can help maintain price stability and provide economic benefits for farmers. From the overall analysis, agricultural subsidies in Southeast Asia have a complex and diverse impact on rice productivity and prices. While subsidies help maintain price stability and support farmers' welfare, their impact on rice productivity still needs to be further eval_uated to ensure more efficient and sustainable allocations. Governments in the region need to continue to review and adjust their subsidy policies in order to strike a balance between supporting smallholders, increasing productivity, and maintaining rice price stability, while minimizing negative impacts on markets and the environment.